2007
DOI: 10.1039/b614267b
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic promotion of gold/titania for CO oxidation by sulfate ions

Abstract: The activity of gold/titania catalysts for the room-temperature oxidation of CO can be dramatically enhanced by the addition of sulfate ions to the support; it appears that anion promotion of gold may be a general phenomenon and may be related to the direct modification of active gold sites in the case of sulfate ions, as evidenced by secondary ion mass spectrometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 25 publications
(25 reference statements)
3
39
2
Order By: Relevance
“…Au/TiO 2 samples were calcined at 400 • C which still retained high amount of sulfate groups on the surface. In contrast to the works of Mohapatra et al, no sulfate species were found in samples prepared by Hidalgo et al, suggesting that different mechanisms would be operative in different reaction conditions [87,88]. The transient absorption decay measurement of Au/TiO 2 at = 675 nm under UV pulse illumination ( = 308 nm) showed less intense signal compared to pure TiO 2 , which was interpreted as indication of accumulation of high number of CB electrons in the Au nanoparticles [89].…”
Section: Photocatalytic Activity Of Gold Deposited Titania (Au/tio 2 )contrasting
confidence: 49%
See 1 more Smart Citation
“…Au/TiO 2 samples were calcined at 400 • C which still retained high amount of sulfate groups on the surface. In contrast to the works of Mohapatra et al, no sulfate species were found in samples prepared by Hidalgo et al, suggesting that different mechanisms would be operative in different reaction conditions [87,88]. The transient absorption decay measurement of Au/TiO 2 at = 675 nm under UV pulse illumination ( = 308 nm) showed less intense signal compared to pure TiO 2 , which was interpreted as indication of accumulation of high number of CB electrons in the Au nanoparticles [89].…”
Section: Photocatalytic Activity Of Gold Deposited Titania (Au/tio 2 )contrasting
confidence: 49%
“…Surface gold metallization would increase the charge separation and thus the efficiency of photocatalytic process. Mohapatra et al, have also found an increased activity of Au/titania catalyst prepared by using sulfate pretreated titanium oxide for the oxidation of CO at room temperature [88]. These authors attributed the higher activity to a direct interaction between sulfate ions with the gold atoms.…”
Section: Photocatalytic Activity Of Gold Deposited Titania (Au/tio 2 )mentioning
confidence: 80%
“…Analogously, Guczi et al post deposited active FeO x layers onto Au/ SiO 2 /Si(100) by pulsed laser deposition, and found that the activity of the FeO x /Au/SiO 2 /Si(100) model catalyst was higher than those of Au/SiO 2 /Si(100) and FeO x / SiO 2 /Si(100) because of the creation of gold-FeO x interface [54]. Others and us have post modified Au/ TiO 2 by nitrate [55], sulfate [56], and phosphate [57] to study the anion effects on activity. Lu and coworkers very recently reported that the impregnation of Au/C with KNO 3 could stabilize gold particles for selective CO oxidation in hydrogen-rich gas [58].…”
Section: Stability and Regeneration Of Sio 2 /Au/tiomentioning
confidence: 94%
“…Modification of the titania with different anions such as SO 2− 4 , PO 3− 4 , and WO 2− 4 has been found to enhance the acidity and certain other physicochemical properties of the catalyst, such as thermal stability and mesoporosity [34][35][36]. In particular, sulfation of semiconductor photocatalysts is of great interest for scientists and engineers because it has an enormous potential for environmental pollutant remediation [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%